Effect of Profitability, Liquidity and Asset Structure on Capital Structure at Ptpn IV Persero Medan - Annisa, Wan Nurul Fatin; Yafiz, Muhammad; Lubis, Arnida Wahyuni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study examines how the capital structure of PTPN IV Persero Medan is influenced by profitability, liquidity, and asset structure. Methodology: The study uses quantitative research methods. Data analysis techniques include Classical Assumptions Test, Multiple Linear Regression Analysis, and Hypothesis Testing using SPSS 26 software. The data used is secondary, specifically the financial statements of PTPN IV Persero Medan from 2008–2020 obtained from the company's website. Results: The findings indicate that profitability (Return on Assets) has minimal and insignificant impact on capital structure (Debt Equity Ratio). Liquidity (current ratio) has a significant negative effect on capital structure. Asset structure also significantly and negatively influences capital structure. Findings: Profitability, liquidity, and asset structure together do not significantly impact capital structure. The coefficient of determination (R2) test results show that profitability, liquidity, and asset structure account for 30.8% of the variation in capital structure, with the remaining influenced by other factors not examined in this study. Novelty: This research provides insights into the specific factors influencing the capital structure of PTPN IV Persero Medan. Originality: The study offers a detailed analysis of the interplay between profitability, liquidity, asset structure, and capital structure in a specific corporate context. Conclusions: Profitability, liquidity, and asset structure collectively have a modest influence on capital structure, highlighting the role of other external factors. Type of Paper: Empirical Research Article